What peacekeeping leaves behind: evaluating the effects of multi-dimensional peace operations in Africa. Issue 1 (2nd January 2017) - Brosig, Malte; Sempijja, Norman
Abstract: Peacekeeping today has become ever more complex reaching deep into conflict affected societies aiming to facilitate social, economic and political transformative processes in order to establish sustainable peace. However, most quantitative studies evaluate mission effectiveness only in terms of conflict abatement. This leaves a substantial assessment gap. Therefore this study explores the effects of multi-dimensional peacekeeping by using 12 governance indicators. The article finds that its ambitious goals have largely not been fulfilled. Although there are measureable effects on national security and political participation, in other areas such as personal safety, human development or public management the impact is minimal or non-existent. In order to explain variation across cases and indicators we are testing four intervening variables: the type of peacekeeping mission, the amount of resources allocated, the relative size of civilian and police units per missions and the relationship between personal safety and governance indicators.